2017
DOI: 10.1016/j.bbrc.2017.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Affinity and path of binding xylopyranose unto E. coli xylose permease

Abstract: Glucose transporters (GLUTs), expressed in all types of human cells, are responsible for the uptake of sugars as the primary energy source for the normal functions of good cells and for the abnormal growth of cancer cells. The E. coli xylose permease (XylE), a homologue of human GLUTs, has been investigated more thoroughly than other major facilitator proteins in the current literature. In this paper, we present a molecular dynamics (MD) study of an all-atom model system to elucidate the atomistic details and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Recent works have used this technique to study the following targets: focal adhesion kinase, 220 the cancer target LSD1, 221 neuraminidase, 222 FK506 binding protein together with trypsin and cyclin-dependent kinase 2, 223 xylose permease, 224 and enzyme 5-enolpyruvylshikimate 3 phosphate synthase. 225 Summarizing this section, absolute binding energy computations are now computationally feasible, up to the accuracy limit of existing force fields, and of finite sampling of the relevant phase space.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent works have used this technique to study the following targets: focal adhesion kinase, 220 the cancer target LSD1, 221 neuraminidase, 222 FK506 binding protein together with trypsin and cyclin-dependent kinase 2, 223 xylose permease, 224 and enzyme 5-enolpyruvylshikimate 3 phosphate synthase. 225 Summarizing this section, absolute binding energy computations are now computationally feasible, up to the accuracy limit of existing force fields, and of finite sampling of the relevant phase space.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…Recent works have used this technique to study the following targets: focal adhesion kinase, the cancer target LSD1, neuraminidase, FK506 binding protein together with trypsin and cyclin-dependent kinase 2, xylose permease, and enzyme 5-enolpyruvylshikimate 3 phosphate synthase …”
Section: Applicationsmentioning
confidence: 99%
“…Interestingly, in two recent studies, the structure and activities of GLUTs were shown to depend on the membrane lipid composition [54] and lipid (fluid/gel) phase [55]. In contrast, most MD simulations on GLUTs of the current literature [51][52][53][55][56][57] have the cell membrane modelled as a symmetric bilayer of a single lipid type.…”
Section: Graphical Abstract Introductionmentioning
confidence: 96%
“…Most molecular dynamics (MD) simulations, e.g., (44)(45)(46)(47), were focused on conforming with the alternating access theory (1,48) that is thought to be universally applicable for all MFS transporters including GLUT1. All these and most other MD simulations on GLUTs (44)(45)(46)(47)(49)(50)(51) have the cell membrane modelled as a symmetric bilayer of a single lipid type. They do not heed the known facts that the structure and activities of GLUTs are sensitive to the membrane lipid compositions.…”
Section: Introductionmentioning
confidence: 99%
“…In light of all these, surveying the current literature of molecular dynamics (MD) simulations of GLUT1, e.g., [46,[54][55][56][57][58], and some other GLUTs [55][56][57][58][59][60][61], one can see the need to further the current MD studies by modelling a cell membrane with two asymmetries between the intracellular (IC) and the extracellular (EC) sides of the membrane: (1) asymmetric lipid compositions of the inner and the outer leaflets and (2) asymmetric saline compositions of the aqueous compartments on the IC and the EC sides of the membrane. A recent MD study [46] included the asymmetry of the first type mimicking the lipid compositions of human erythrocyte.…”
Section: Introductionmentioning
confidence: 99%